2015
DOI: 10.1159/000439357
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Chemotherapy for Retinoblastoma: A Single-Center Experience

Abstract: Background: Studies conducted in recent years have reported promising results regarding the treatment of retinoblastoma with the intra-arterial use of melphalan. In the present study, we intended to report the results of intra-arterial chemotherapy with melphalan (IACT) in the treatment of newly diagnosed or relapsed-refractory retinoblastoma patients at the Department of Pediatric Oncology of Hacettepe University, Ankara, Turkey. Materials and Methods: This was a retrospective study of patients with intraocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Apart from these, no other systemic adverse events were observed [21]. Interestingly, Akyuz et al did not detect any systemic side effects in their study [33] which is in agreement with findings published by Parareda et al [32]. Abramson et al found that bronchospasm was the most common systemic complication during intraarterial drug delivery and occurred in 44 patients [22].…”
Section: Systemic/extraocular Complicationssupporting
confidence: 81%
See 4 more Smart Citations
“…Apart from these, no other systemic adverse events were observed [21]. Interestingly, Akyuz et al did not detect any systemic side effects in their study [33] which is in agreement with findings published by Parareda et al [32]. Abramson et al found that bronchospasm was the most common systemic complication during intraarterial drug delivery and occurred in 44 patients [22].…”
Section: Systemic/extraocular Complicationssupporting
confidence: 81%
“…Following enucleation, both patients died as the disease progressed despite intensive treatment with radiotherapy and chemotherapy [33]. One patient developed brain metastases [33]. In the other patient, metastatic spread was not specified by the authors [33].…”
Section: Metastasis Death and Secondary Cancersmentioning
confidence: 97%
See 3 more Smart Citations